Preparation method and application of hollow amorphous high-entropy oxide self-supporting electrode material

CN122898908APending Publication Date: 2026-10-13JIMEI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611209366.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-11
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

[0005]本发明的目的还在于提供该中空非晶态高熵氧化物自支撑电极材料的应用,是将该中空非晶态高熵氧化物自支撑电极材料作为析氧反应的电催化剂,解决现有高熵析氧催化剂难以兼顾高活性与长循环稳定性、无法适配淡水及海水复杂电解工况的问题,提升电催化剂在不同水系环境下的服役稳定性与工况适配性,为高性能、低成本电解水制氢技术的工业化应用提供技术支撑

Benefits of technology

1、本发明通过水热体系下多金属离子协同刻蚀氧化锌纳米棒,原位构建兼具非晶相与中空结构的高熵材料,材料的大比表面积与高无序度结构可加速电化学重构;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122898908A_ABST
    Figure CN122898908A_ABST
Patent Text Reader

Abstract

The application discloses a preparation method and application of a hollow amorphous high-entropy oxide self-supporting electrode material, and is characterized in that carbon paper is used as a conductive substrate, and zinc oxide nanorods are used as a sacrifice template to design a hollow and self-supporting amorphous ZnFeCoNiCu oxide (H-ZFCNC-O). The hollow structure realizes a double-side electrolyte diffusion channel. Meanwhile, the amorphous matrix eliminates a long-range diffusion obstacle, and a multi-element synergistic effect forms a multi-path reconstruction mechanism. Therefore, the H-ZFCNC-O exhibits accelerated reconstruction kinetics, forms a high-activity phase, overcomes a diffusion retardation effect through structural amorphization, and more effectively drives electrochemical reconstruction of high-configuration entropy, so that a new strategy is provided for regulating structural evolution of a high-entropy electrocatalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of electrocatalytic materials technology, specifically to a method for preparing a hollow amorphous high-entropy oxide self-supporting electrode material and its application. Background Technology

[0002] High-entropy metal electrocatalysts can uniformly fuse five or more metal elements, possessing a continuously tunable electronic structure and widely distributed adsorption sites, providing optimal binding energies for key oxygen-containing intermediates in the oxygen evolution reaction (OER). Previous studies have shown that the surface of high-entropy metal electrocatalysts can undergo simultaneous reconstruction of multiple metal species, generating in-situ homogeneous and structurally disordered high-entropy hydroxide or hydroxyl oxide active phases. However, the inherent atomic-level structural disorder of high-entropy materials significantly inhibits cation migration, resulting in electrochemical reconstruction being limited to the near-surface region. While this diffusion retardation effect ensures high structural stability of the electrocatalyst during electrochemical reconstruction, it leads to insufficient formation of active sites and a lag in activation kinetics, ultimately resulting in limited catalytic activity enhancement.

[0003] Structural amorphization can construct short-range disordered structures with numerous lattice defects, loose atomic arrangements, and flexible coordination environments. This unique structure can overcome diffusion retardation effects, reduce the migration energy barriers of metal ions and oxygen species, and significantly promote the homogeneous structural evolution of catalysts during electrochemical reactions, enabling the catalyst to generate a large number of stable high-entropy active phases. The strong electronic effects and geometric synergistic effects among the metal components within the phases can effectively enhance the intrinsic catalytic activity of the material. Therefore, structural amorphization is a rational and efficient modification strategy for regulating the reconstruction kinetics of high-entropy catalysts and improving their oxygen evolution reaction catalytic activity. Summary of the Invention

[0004] The purpose of this invention is to provide a method for preparing a hollow amorphous high-entropy oxide self-supporting electrode material, which employs a co-etching induced amorphization strategy to prepare the hollow amorphous high-entropy oxide self-supporting electrode material.

[0005] The present invention also aims to provide an application for the hollow amorphous high-entropy oxide self-supporting electrode material, which is used as an electrocatalyst for the oxygen evolution reaction. This addresses the problems of existing high-entropy oxygen evolution catalysts, such as their inability to balance high activity and long-term cycle stability, and their inability to adapt to the complex electrolysis conditions of freshwater and seawater. It improves the service stability and adaptability of the electrocatalyst in different water systems, providing technical support for the industrial application of high-performance, low-cost water electrolysis hydrogen production technology.

[0006] To achieve the above objectives, the solution of the present invention is: A method for preparing a hollow amorphous high-entropy oxide self-supporting electrode material includes the following steps: Step 1, Carbon Paper (CP) Pretreatment: First, cut the CP into CP sheets with a size of 1cm × 2cm. Then, clean them with deionized water and ethanol alternately using ultrasonic cleaning multiple times to remove oxides and impurities attached to the surface of the CP sheets. Dry them for later use. Step 2: Hydrothermal synthesis of ZnO nanorod precursor / CP precursor: Then, 0.4-0.6 g zinc nitrate, 0.1-0.3 g hexamethyltetramine and 1-3 mL ammonia were dissolved in 40-60 mL deionized water, and the pretreated CP sheet from step 1 was added. The mixture was then transferred to a 50 mL high-pressure reactor and hydrothermally reacted at 80-120 °C for 10-14 hours. The resulting reactants were then washed with deionized water and ethanol to remove surface deposits and dried to obtain ZnO nanorod precursor / CP precursor. Step 3: Hydrothermal synthesis of hollow amorphous high-entropy oxide self-supporting electrode material: Then, 0.1-0.2 g of cobalt nitrate, 0.1-0.2 g of nickel nitrate, 0.1-0.2 g of copper nitrate, 0.15-0.25 g of ferric nitrate, and 0.045-0.055 g of urea were completely dissolved in 40-60 mL of deionized water. The ZnO nanorod precursor / CP precursor prepared in step 2 was added, and the mixture was transferred to a 50 mL high-pressure reactor. The mixture was hydrothermally reacted at 110-130 °C for 5-7 hours. The resulting reactants were then washed sequentially with deionized water and ethanol to remove surface deposits, dried, and finally placed in a muffle furnace and heated to 300-400 °C at a heating rate of 4-6 °C / min. The temperature was maintained for 1-3 hours to obtain the hollow amorphous high-entropy oxide electrode material (denoted as H-ZFCNC-O electrode material).

[0007] In step 1, each ultrasonic cleaning session lasts 10 to 30 minutes.

[0008] In steps 1 to 3, the drying temperature is 60°C and the drying time is 6 to 8 hours.

[0009] In step 1, the zinc nitrate is zinc nitrate hexahydrate; in step 2, the cobalt nitrate is cobalt nitrate hexahydrate, the nickel nitrate is nickel nitrate hexahydrate, the copper nitrate is copper nitrate trihydrate, and the ferric nitrate is ferric nitrate nonahydrate.

[0010] One application of a hollow amorphous high-entropy oxide self-supporting electrode material is as an electrocatalyst for the oxygen evolution reaction.

[0011] The preparation method of the H-ZFCNC-O electrode material of this invention adopts a co-etching induced amorphization strategy, and its preparation schematic diagram is shown below. Figure 1As shown, zinc oxide nanorods were first grown on a CP substrate using a hydrothermal method, which served as a sacrificial template. Subsequently, the CP substrate loaded with zinc oxide nanorods was placed in a mixed salt solution containing trivalent iron, divalent cobalt, divalent nickel and divalent copper ions for a second hydrothermal treatment. Under high temperature and self-generated pressure hydrothermal environment, various metal ions will selectively etch zinc oxide nanorods, causing zinc oxide to dissolve and simultaneously release zinc ions. It is worth noting that the template-induced epitaxial growth effect can make zinc oxide nanorods act as structure guiding agents, guiding multi-metal components to complete nucleation and initial atomic assembly, thereby directly generating an amorphous oxide shell on the surface of the nanorods. Ultimately, the four types of metal ions co-precipitate with the dissolved zinc ions. After calcination, due to the difference in the dissolution rate of zinc oxide and the precipitation rate of the multi-metal components, the original positions of the zinc oxide nanorods eventually form hollow cavities, and the outer layer is composed of the generated amorphous high-entropy oxide, thus obtaining high-entropy zinc-iron-cobalt-nickel-copper oxide (H-ZFCNC-O).

[0012] By adopting the above technical solution, the preparation method of the hollow amorphous high-entropy oxide self-supporting electrode material of the present invention and its application have the following beneficial effects: 1. This invention constructs a high-entropy material with both amorphous phase and hollow structure in situ by synergistic etching of zinc oxide nanorods by multiple metal ions in a hydrothermal system. The large specific surface area and high disorder structure of the material can accelerate electrochemical reconstruction. 2. The H-ZFCNC-O electrode material effectively overcomes the problem of ion diffusion hindrance in traditional crystalline high-entropy materials by utilizing the characteristics of amorphous loose structure, significantly reducing the migration energy barrier of metal ions and oxygen species, promoting the catalyst to change from local reconstruction on the surface to overall uniform reconstruction, fully activating the hidden active sites in the bulk phase, and effectively improving the drawbacks of slow activation kinetics and insufficient utilization of active sites in high-entropy catalysts. 3. The H-ZFCNC-O electrode material couples the hollow multi-level structure with the synergistic effect of high-entropy multi-metals. Relying on the rich lattice defects and flexible coordination environment of the amorphous structure, it significantly optimizes the adsorption and desorption behavior of oxygen evolution reaction intermediates, reduces the intrinsic energy barrier of the reaction, and enables the catalyst to have extremely low oxygen evolution overpotential in both freshwater and simulated seawater systems, thus greatly improving the intrinsic electrocatalytic oxygen evolution activity. 4. The H-ZFCNC-O electrode material can generate a structurally stable high-entropy active phase through amorphization-induced reconstruction, which effectively avoids the problems of structural collapse and activity decay during long-term electrolysis of traditional high-entropy catalysts, significantly extends the cycle service life of the catalyst, and achieves a synergistic unity of high activity and high structural stability. 5. The H-ZFCNC-O electrode material has a self-supporting structure. The carbon paper mainly serves as a conductive substrate, current collector, and mechanical support. No additional binder or conductive agent is needed, and it can be used directly as a working electrode, simplifying the electrode preparation process and improving structural stability. Attached Figure Description

[0013] Figure 1 This is a schematic diagram of the preparation of the H-ZFCNC-O electrode material; Figure 2 The images show the electron microscope (EM) morphology of the H-ZFCNC-O electrode material prepared in Example 1, where (a) is the scanning electron microscope (SEM) morphology of the H-ZFCNC-O electrode material, (b) is the transmission electron microscope (TEM) morphology of the H-ZFCNC-O electrode material, (c) is the lattice analysis of the H-ZFCNC-O electrode material, and (d) is the EDS transmission image of the H-ZFCNC-O electrode material. Figure 3 The figures are characterization diagrams of the electrode materials, where (a) is the XRD pattern of the H-ZFCNC-O electrode material prepared in Example 1, (b) is the XRD pattern of the D-ZFCNC-O electrode material prepared in Comparative Example 1, and (c) is the Raman spectrum of the ZnO, H-ZFCNC-O, and D-ZFCNC-O electrode materials. Figure 4 The specific surface area and pore size distribution of the H-ZFCNC-O electrode material prepared in Example 1 and the D-ZFCNC-O prepared in Comparative Example 1 are shown in (a) and (b) respectively. Figure 5 Linear scan voltammetry obtained from Application Example 1 (corresponding to H-ZFCNC-O electrode material) and Application Example 2 (corresponding to D-ZFCNC-O electrode material); Figure 6 The long-cycle stability diagram is for Application Example 1 (corresponding to H-ZFCNC-O electrode material); Figure 7 Linear scan voltammetry of the AEM electrolytic cell for application example 1 (corresponding to H-ZFCNC-O electrode material); Figure 8 The diagram shows the long-cycle stability of the AEM electrolyzer using Example 1 (corresponding to H-ZFCNC-O electrode material). Detailed Implementation

[0014] To further explain the technical solution of the present invention, the present invention will be described in detail below through specific embodiments.

[0015] I. Preparation of Electrode Materials Example 1 A method for preparing a hollow amorphous high-entropy oxide self-supporting electrode material includes the following steps: Step 1, CP preprocessing: First, cut the CP into CP sheets with a size of 1cm × 2cm. Then, clean them twice with deionized water and ethanol alternately, with each ultrasonic cleaning time being 30 minutes, to remove the oxides and impurities attached to the surface of the CP sheets. Dry them at 60℃ for 7 hours for later use. Step 2: Hydrothermal synthesis of ZnO nanorod precursor / CP precursor: Then, 0.446 g of zinc nitrate hexahydrate, 0.21 g of hexamethyltetramine and 2 mL of ammonia were dissolved in 50 mL of deionized water, and the pretreated CP sheet from step 1 was added. The mixture was then transferred to a 50 mL high-pressure reactor and hydrothermally reacted at 90 °C for 12 hours. The resulting reactants were then washed with deionized water and ethanol to remove surface deposits and dried at 60 °C for 7 hours to obtain ZnO nanorod precursor / CP precursor. Step 3: Hydrothermal synthesis of hollow amorphous high-entropy oxide self-supporting electrode material: Then, 0.1455g of cobalt nitrate hexahydrate, 0.1454g of nickel nitrate hexahydrate, 0.1208g of copper nitrate trihydrate, 0.2020g of ferric nitrate nonahydrate, and 0.0492g of urea were completely dissolved in 50 mL of deionized water. The ZnO nanorod precursor / CP precursor prepared in step 2 was added, and the mixture was transferred to a 50 mL high-pressure reactor. The mixture was hydrothermally reacted at 120℃ for 6 hours. The resulting reactants were then washed sequentially with deionized water and ethanol to remove surface deposits. The reactants were dried at 60℃ for 7 hours. Finally, the reactants were placed in a muffle furnace and heated to 350℃ at a heating rate of 5℃ / min, and held at that temperature for 2 hours to obtain the hollow amorphous high-entropy oxide electrode material (denoted as H-ZFCNC-O electrode material).

[0016] Comparative Example 1 A method for preparing a crystalline high-entropy oxide self-supporting electrode material includes the following steps: Step 1, CP preprocessing: First, cut the CP into CP sheets with a size of 1cm × 2cm. Then, clean them twice with deionized water and ethanol alternately, with each ultrasonic cleaning time being 30 minutes, to remove the oxides and impurities attached to the surface of the CP sheets. Dry them at 60℃ for 7 hours for later use. Step 2: Hydrothermal synthesis of crystalline high-entropy oxide self-supporting electrode material: Then, 0.446 g zinc nitrate hexahydrate, 0.1455 g cobalt nitrate hexahydrate, 0.1454 g nickel nitrate hexahydrate, 0.1208 g copper nitrate trihydrate, 0.2020 g ferric nitrate nonahydrate, and 0.0492 g urea were completely dissolved in 50 mL of deionized water. The CP sheet prepared in step 1 was added, and the mixture was transferred to a 50 mL high-pressure reactor. The reaction was carried out hydrothermally at 120 °C for 6 hours. The resulting reactants were then washed with deionized water and ethanol to remove surface deposits. The reactants were dried at 60 °C for 7 hours. Finally, the reactants were placed in a muffle furnace and heated to 350 °C at a heating rate of 5 °C / min, and held at that temperature for 2 hours to obtain the crystalline high-entropy oxide electrode material (denoted as D-ZFCNC-O electrode material).

[0017] II. Application of Electrode Materials Application Example 1 The H-ZFCNC-O electrode material prepared in Example 1 was used as an electrocatalyst for electrochemical performance testing. All tests were conducted using a three-electrode system controlled by a CHI660F electrochemical workstation, with the reference electrode being an Ag / AgCl electrode and the counter electrode being a 1 cm electrode. 2 Platinum sheet, working electrode is 1cm 2 The H-ZFCNC-O electrode material uses a 1 M KOH solution as the electrolyte.

[0018] Application Example 2 The D-ZFCNC-O electrode material prepared in Comparative Example 1 was used as an electrocatalyst for electrochemical performance testing. All tests were conducted using a three-electrode system controlled by a CHI660F electrochemical workstation, with the Ag / AgCl electrode as the reference electrode and a 1 cm electrode as the counter electrode. 2 Platinum sheet, working electrode is 1cm 2 The H-ZFCNC-O electrode material uses a 1 M KOH solution as the electrolyte.

[0019] III. Characterization of Electrode Materials 1. SEM and TEM characterization The morphology was observed using a scanning electron microscope (SEM, Zeiss 550). Figure 2 (a) shows that the H-ZFCNC-O electrode material has a hollow tubular structure assembled from irregular nanoparticles. More importantly, the selective etching of the zinc oxide template forms a hollow structure, which can increase the specific surface area and pore volume of the material. This hollow structure can expose more metal sites and promote electrolyte penetration, ultimately achieving more complete and kinetically superior surface reconstruction during electrochemical activation.

[0020] Figure 2(b) Transmission electron microscopy (TEM, FEI Talos F200X) images further confirm that the H-ZFCNC-O electrode material is a hollow structure formed by the stacking of irregular nanoparticles; Figure 2 (c) No clear and regular periodic lattice fringes were observed, proving that the H-ZFCNC-O electrode material has no long-range crystal order and belongs to amorphous material.

[0021] This amorphous characteristic originates from the random occupancy of various metal atoms in high-entropy oxides, and the significant differences in the size of different metal atoms inhibit the formation of long-range ordered lattices, thus exhibiting amorphous characteristics with disordered atomic arrangement.

[0022] Figure 2 (d) The EDS elemental mapping shows that all elements are distributed only in the tube wall region, which matches the morphology space observed by TEM. All types of elements are uniformly dispersed in the tube wall, and there is no element segregation or local enrichment phenomenon, which proves that the H-ZFCNC-O electrode material is a single-phase solid solution and the components are uniformly mixed at the atomic scale.

[0023] 2. XRD and Raman characterization Figure 3 (a) is the X-ray diffraction (XRD) pattern of the phase evolution during the hydrothermal synthesis of the H-ZFCNC-O electrode material in Example 1. It can be clearly observed from the figure that the initial zinc oxide substrate exhibits strong diffraction peaks at 31.7°, 34.3°, and 36.2°. In the XRD pattern of the sample taken during the middle stage of the hydrothermal reaction and then calcined, the intensity of the zinc oxide diffraction peaks decreased, while characteristic peaks of metal oxides appeared. This proves that the product obtained when the hydrothermal reaction was incomplete possesses significant crystallinity after calcination. XRD testing of the H-ZFCNC-O product obtained after a complete hydrothermal reaction showed no characteristic peaks of zinc oxide or any single-component metal oxide in the spectrum, indicating that the zinc oxide had completely dissolved, and the product formed an amorphous phase structure.

[0024] from Figure 3 (b) It can be seen that the zinc-iron-cobalt-nickel-copper high-entropy oxide (D-ZFCNC-O) synthesized directly by one-step hydrothermal method exhibits sharp diffraction peaks and high crystallinity, which is not conducive to the exposure of defects and metal active sites.

[0025] like Figure 3 As shown in (c), the H-ZFCNC-O electrode material at 470 cm⁻¹ -1 and 671 cm -1 A broad and diffuse Raman characteristic peak appears at 554 cm⁻¹, which is attributed to the metal-oxygen (MO) bond vibration mode. In contrast, the D-ZFCNC-O electrode material exhibits the sharp, well-defined characteristic peaks typical of crystalline metal oxides, with a peak at 554 cm⁻¹.-1 An additional Raman peak appears, corresponding to the stretching vibration of the nickel-oxygen bond in nickel oxide.

[0026] 3. Specific surface area and pore size distribution: By comparing and analyzing N2 adsorption-desorption isotherms and pore size distributions, the specific surface area and pore size distribution of H-ZFCNC-O and D-ZFCNC-O electrode materials were investigated. Figure 4 (a) The specific surface area of ​​the H-ZFCNC-O electrode material is shown to be 20.95 m². 2 / g, which is much larger than the specific surface area of ​​the D-ZFCNC-O electrode material (8.28 m²). 2 / g), which is due to the hollow amorphous structure of the H-ZFCNC-O electrode material, which significantly increases its specific surface area. Figure 4 As shown in the pore size distribution diagram in (b), the pore size distribution of the H-ZFCNC-O electrode material is mainly in the range of 2~5 nm. Both of these electrode materials are rich in mesopores. The abundance of mesopores is beneficial to improving charge transport efficiency, while the large specific surface area can provide a large number of active sites and improve catalytic reaction efficiency.

[0027] IV. Electrochemical Performance Testing of Electrode Materials 1. Using the H-ZFCNC-O electrode material prepared in Example 1 as a catalyst, electrochemical performance was tested. For example... Figure 5 As shown, the H-ZFCNC-O electrode material at 50 mA cm⁻¹ -2 and 100 mA cm -2 It can achieve low overpotentials of 274 mV and 315 mV respectively, exhibiting the highest OER activity among all tested catalysts.

[0028] As shown in Figure (6), the OER potential of the H-ZFCNC-O electrode material is at 100 mA cm⁻¹. -2 Continuous operation for 160 hours and at 500mA cm -2 After 190 hours of continuous operation, no significant degradation was observed. In summary, the excellent OER performance of the H-ZFCNC-O electrode material is attributed to the rapid reconstruction behavior driven by its amorphous and high-entropy configuration. This reconstruction generates a large number of catalytically active species with high disorder, high entropy, and abundant oxygen vacancies.

[0029] 2. Using the H-ZFCNC-O electrode material prepared in Example 1 as a catalyst, an H-ZFCNC-O ||ZnO@CoMoO4 anion exchange membrane (AEM) electrolyzer was assembled for water splitting. As shown in Figure (7), the AEM electrolyzer was operated at a current density of 100 mAcm⁻¹. -2The voltage corresponding to this is 1.769 volts. The lower the voltage of the electrolyzer at a specific current density, the lower its energy consumption and the better its water electrolysis performance. As shown in Figure (8), at 100 mA cm⁻¹ -2 After 100 hours of stable operation, the voltage decay rate is only 0.21 mV / h. -1 At 200 mA cm 2 The electrode maintained stable output for 100 hours under high current density, demonstrating its excellent catalytic performance, electrochemical durability, and promising industrial application prospects in practical electrocatalytic systems.

[0030] This invention reveals the intrinsic mechanism by which the H-ZFCNC-O self-supporting hollow amorphous high-entropy oxide electrode material exhibits excellent performance through material characterization and electrochemical testing: 1. Amorphous disordered lattice regulates electronic coordination environment: Unlike the long-range ordered lattice structure of one-step crystalline nanoneedle high-entropy oxides, the atomic arrangement of amorphous structure is random and disordered, and the metal atom size mismatch is large. It can generate a large number of unsaturated coordination sites, lattice vacancies and surface defects, effectively optimize the electronic structure of metal sites, reduce the energy barrier of electrocatalytic reaction, and at the same time, it can efficiently drive electrochemical in-situ self-reconstruction and generate highly active hydroxyl oxide active interface in-situ. 2. Hollow mesoporous structure constructs an efficient mass transfer system: The material's unique hollow cavity combined with the particle-packed mesoporous channels greatly increases the material's specific surface area and exposes the multi-metal active sites inside and outside the tube wall in all directions; at the same time, the interconnected porous channels can shorten the migration path of electrolyte ions and reaction intermediates, enhance the electrolyte's wetting and penetration ability, accelerate the interfacial charge transfer, and significantly optimize the catalytic reaction kinetics. 3. High-entropy synergistic effect coupled with hollow structure to improve structural stability: The high-entropy effect of the five-element metal solid solution of Zn, Fe, Co, Ni and Cu has a strong element synergistic effect, which can optimize the electron transfer between metals; at the same time, the hollow cavity has a spatial buffering effect, which can offset the volume deformation stress caused by long-term electrocatalytic cycling and interface reconstruction, inhibit the agglomeration and collapse of nanoparticles, and effectively improve the long-term cycling stability of electrode materials.

[0031] The above embodiments and figures are not intended to limit the product form and style of the present invention. Any appropriate changes or modifications made by those skilled in the art should be considered as not departing from the patent scope of the present invention.

Claims

1. A method for preparing a hollow amorphous high-entropy oxide self-supporting electrode material, characterized in that: Includes the following steps: Step 1, CP preprocessing: First, cut the CP into CP sheets with a size of 1cm × 2cm. Then, clean them with deionized water and ethanol alternately using ultrasonic cleaning multiple times to remove oxides and impurities attached to the surface of the CP sheets. Dry them for later use. Here, CP represents carbon paper. Step 2: Hydrothermal synthesis of ZnO nanorod precursor / CP precursor: Then, 0.4-0.6 g zinc nitrate, 0.1-0.3 g hexamethyltetramine and 1-3 mL ammonia were dissolved in 40-60 mL deionized water, and the pretreated CP sheet from step 1 was added. The mixture was then transferred to a 50 mL high-pressure reactor and hydrothermally reacted at 80-120 °C for 10-14 hours. The resulting reactants were then washed with deionized water and ethanol to remove surface deposits and dried to obtain ZnO nanorod precursor / CP precursor. Step 3: Hydrothermal synthesis of hollow amorphous high-entropy oxide self-supporting electrode material: Then, 0.1-0.2 g of cobalt nitrate, 0.1-0.2 g of nickel nitrate, 0.1-0.2 g of copper nitrate, 0.15-0.25 g of ferric nitrate, and 0.045-0.055 g of urea were completely dissolved in 40-60 mL of deionized water. The ZnO nanorod precursor / CP precursor prepared in step 2 was added, and the mixture was transferred to a 50 mL high-pressure reactor. The mixture was hydrothermally reacted at 110-130 °C for 5-7 hours. The resulting reactants were then washed sequentially with deionized water and ethanol to remove surface deposits, dried, and finally placed in a muffle furnace and heated to 300-400 °C at a heating rate of 4-6 °C / min, and held at that temperature for 1-3 hours to obtain the hollow amorphous high-entropy oxide electrode material.

2. The method for preparing a hollow amorphous high-entropy oxide self-supporting electrode material according to claim 1, characterized in that: In step 1, each ultrasonic cleaning session lasts 10 to 30 minutes.

3. The method for preparing a hollow amorphous high-entropy oxide self-supporting electrode material according to claim 1, characterized in that: In steps 1 to 3, the drying temperature is 60°C and the drying time is 6 to 8 hours.

4. The method for preparing a hollow amorphous high-entropy oxide self-supporting electrode material according to claim 1, characterized in that: In step 1, the zinc nitrate is zinc nitrate hexahydrate; in step 2, the cobalt nitrate is cobalt nitrate hexahydrate, the nickel nitrate is nickel nitrate hexahydrate, the copper nitrate is copper nitrate trihydrate, and the ferric nitrate is ferric nitrate nonahydrate.

5. An application of a hollow amorphous high-entropy oxide self-supporting electrode material, characterized in that: The hollow amorphous high-entropy oxide self-supporting electrode material prepared by the preparation method described in claim 1 is used as an electrocatalyst for the oxygen evolution reaction.